2014
DOI: 10.4049/jimmunol.1400375
|View full text |Cite
|
Sign up to set email alerts
|

Superimposed Epitopes Restricted by the Same HLA Molecule Drive Distinct HIV-Specific CD8+ T Cell Repertoires

Abstract: Superimposed epitopes, in which a shorter epitope is embedded within a longer one, can be presented by the same HLA class I molecule. CD8+ CTL responses against such epitopes and the contribution of this phenomenon to immune control are poorly characterized. In this study, we examined HLA-A*24:02–restricted CTLs specific for the superimposed HIV Nef epitopes RYPLTFGWCF (RF10) and RYPLTFGW (RW8). Unexpectedly, RF10-specific and RW8-specific CTLs from HIV-1–infected HLA-A*24:02+ individuals had no overlapping Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…There were no differences between RF10-WT-specific and RF10-2F-specific CTLs in terms of a ( Figure 3B) and b TCR diversity ( Figure 3C). Altogether, these results support the notion that the induction of T cells with high TCR diversity can be driven by a featured epitope in the case of RF10-WT/RF10-2F-specific CTLs (Sun et al, 2014).…”
Section: Distinct Clonotypic Patterns Between Rf10 and Rf10-2f-specifsupporting
confidence: 83%
See 2 more Smart Citations
“…There were no differences between RF10-WT-specific and RF10-2F-specific CTLs in terms of a ( Figure 3B) and b TCR diversity ( Figure 3C). Altogether, these results support the notion that the induction of T cells with high TCR diversity can be driven by a featured epitope in the case of RF10-WT/RF10-2F-specific CTLs (Sun et al, 2014).…”
Section: Distinct Clonotypic Patterns Between Rf10 and Rf10-2f-specifsupporting
confidence: 83%
“…First, we assessed the ability of RW8-or RF10-specific CTL clone established from patient KI-158 to suppress WT and 2F mutant viruses. In line with the higher functional avidity of RF10-specific CTLs Sun et al, 2014), the ability of a representative dominant RF10-specific CTL clone CTL170 to suppress HIV-1 was stronger than that of a representative dominant RW8-specific CTL clone CTL52 ( Figure 1A), suggesting that RF10-specific CTLs may have effectively selected the 2F virus. Nonetheless, in a competitive HIV-1 suppression assay with target cells infected with a mixture of WT and mutant virus at a ratio of 9:1, respectively ( Figure 1B), we did not observe any significant difference in the selection of the 2F mutant between RW8and RF10-specific CTL clones ( Figure 1C), indicating that both CTLs could effectively select 2F viruses.…”
Section: In Vitro Selection Of 2f Mutant By Rw8-or Rf10-specific Ctlsmentioning
confidence: 69%
See 1 more Smart Citation
“…This ‘featureless’ HLA-A2/M1 complex was recognized mainly by residues from CDR1β, CDR2β and Arg 98 of the CDR3β xR 98 S 99 x motif, explaining the biased selection of TRBV19 and the role of the conserved CDR3β motif, with few MHC or peptide contacts from TCRα side chains 14 . It has been suggested that featureless (or less featured) peptides are more prone to TCR bias than featured peptides, because of a dearth of available recognition modes 1517 . Direct proof of this concept came from an elegant study 18 where the highly featured PA 224 epitope from influenza acidic polymerase presented by H-2D b was mutated to a more featureless version, inducing a change from a diverse TCR repertoire to a more restricted one.…”
mentioning
confidence: 99%
“…Recently, several studies in HIV-1 have found HIV-1-specific CD8 T cells expressed these recombination [37,38], and the crystal structures of TCR-pMHC revealed that TRDV1/TRBV TCR was similar to the TRAV/TRBV structures [39]. Recently, several studies in HIV-1 have found HIV-1-specific CD8 T cells expressed these recombination [37,38], and the crystal structures of TCR-pMHC revealed that TRDV1/TRBV TCR was similar to the TRAV/TRBV structures [39].…”
Section: Discussionmentioning
confidence: 99%